A CRITICAL ANALYSIS OF COMMUNICATION ETHICS IN ONLINE JOURNALISM - Loso Judijanto; David Loba; Istiqomah Nur Rahmawati (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This research explores the challenges faced by online journalism practices in managing communication ethics, particularly in the aspects of information accuracy and speed of news distribution. With the increasing influence of social media and digital platforms, online journalism faces growing pressure to publish news quickly, often at the expense of a thorough verification process. This research identifies that one of the main root causes of the problem is the lack of training and strict editorial standards, resulting in errors in reporting and declining public trust in the media. The study conducted in this research used the literature research method. The results found that the practice of communication ethics in online journalism is simply to maintain the integrity of the media and strengthen public trust in an ever-evolving information age.